Fishery report of the krill catching trawler «Cooperation Sea» on the Antarctic krill (Euphausia superba) biology and hydrometeorological conditions in the fishing area of the Atlantic Antarctic during the summer-winter fishing season of 2015 - N.N. Zhuk; Yu. V. Korzun (Ukrainian Antarctic Journal, 2016)
The krill catching trawler «Cooperation Sea» was conducting the Antarctic krill (Euphausia superba) fisheries in the Atlantic Antarctic area (South Shetland Islands, Bransfield Strait and off South Georgia Island) from 7 February to 23 June 2015. The total krill catch made up 12,500 tons, including area 48.1 (10,900 tons) and area 48.3 (1,600 tons); the CPUE parameter equaled 9.1 tons per hour and 7.9 tons per hour, correspondingly; the average catch per boat day reached 119.7 tons and 95.6 tons, correspondingly. It is suggested that the total krill catch in the Atlantic Antarctic in 2016 can be increased by means of krill fisheries in subarea 48.2, where fishing zones had been covered with ice during the last fishing season, or equipping the vessel with continuous fishing system. This system will allow to efficiently catch krill concentrations, which, according to the traditional fishing scheme, is not considered feasible. Commercial krill aggregations were formed in the north-western areas of the island and continental shelf and slope. The krill specimens in the islands’ area (Elephant Island, George Island, Livingston Island) were characterized by a larger size than those caught in the Bransfield Strait. Thus, length and weight of the krill body, caught on the shelf and slope of the islands, ranged from 46.7 to 52.3 mm and from 0.68 to 1.04 g; in the strait area - from 43.6 to 46.7 mm and from 0.53 to 0.59 g, correspondingly. Larger krill specimens were reported in the zones with high surface temperature. In February-March, in the areas of the South Shetland Islands and Bransfield Strait krill spawning sites were observed; its intensive feeding on phytoplankton in the upper ocean layers was also marked. In April-May the krill spawning season was finished: in area 48.1 it came to end later than in area 48.3. For a short period of time, hydrometeorological and ice conditions in areas 48.1 and 48.3 prevented the trawler from conducting fisheries. The loss of fishing time made up 8.8 days, or 7.5% of the total amount of boat days.